Immune-Directed Gene Therapeutic Development for Alzheimer's, Prion, and Parkinson's Diseases - Maguire-Zeiss, Kathleen A. (2008)
The development of novel immune-based therapeutics for neurodegenerative diseases is an area of intense focus. Neurodegenerative diseases represent a particular challenge since in many cases the onset of symptoms occurs after considerable degeneration has ensued. Based on human genetic and histopathological evidence from patients with neurodegenerative diseases, animal models that recapitulate specific pathologic features have been developed. Utilizing these animal models in combination with viral vector-based gene therapeutics, specific epochs of disease can be targeted. One common feature of several neurodegenerative diseases is misfolded proteins. The mechanism by which these altered protein conformers lead to neurodegeneration is not completely understood but much effort has been put forward to either degrade aberrant protein or prevent the formation of misfolded conformers. In this review, we will summarize work that employs viral vector gene therapeutics to modulate the brain's response to misfolded proteins with a specific focus on neurodegeneration.